2022
DOI: 10.1089/heq.2022.0001
|View full text |Cite
|
Sign up to set email alerts
|

“People Like Us”: News Coverage of Food Assistance During the COVID-19 Pandemic

Abstract: Objective: To understand how the public discourse around food assistance and social responsibility evolved during the first year of the COVID-19 pandemic by analyzing news coverage. Methods: We conducted an ethnographic content analysis of news articles and photographs about food insecurity or food assistance published by U.S. newspapers and wire services between December 1, 2019, and November 30, 2020. We analyzed a random sample of 241 articles and 223 photographs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…One of these studies found that insecurity was largely defined as inadequate food quantity and that the term ‘holiday hunger’ was commonly used to define the extent and timing of child food poverty ( Yau et al ., 2021 ). One study found few articles (8%) connecting food access and health ( Mejia et al ., 2022 ). Four studies reported newspaper coverage of physical health implications such as obesity and malnutrition ( Henderson and Foley, 2010 ; Knight et al ., 2018 ; Marín-Murillo et al ., 2020 ; Yau et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of these studies found that insecurity was largely defined as inadequate food quantity and that the term ‘holiday hunger’ was commonly used to define the extent and timing of child food poverty ( Yau et al ., 2021 ). One study found few articles (8%) connecting food access and health ( Mejia et al ., 2022 ). Four studies reported newspaper coverage of physical health implications such as obesity and malnutrition ( Henderson and Foley, 2010 ; Knight et al ., 2018 ; Marín-Murillo et al ., 2020 ; Yau et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine out of 10 studies reported findings on the drivers of food poverty and insecurity presented in newspaper coverage. Across most studies, the immediate drivers of food poverty and insecurity were reported as low income ( Wells and Caraher, 2014 ; Knight et al ., 2018 ; Yau et al ., 2021 ; Mejia et al ., 2022 ) and high cost-of-living ( Henderson and Foley, 2010 ; Wells and Caraher, 2014 ; Knight et al ., 2018 ; Yau et al ., 2021 ), resulting in insufficient income ( Wells and Caraher, 2014 ; Knight et al ., 2018 ; Tikka, 2019 ; Price et al ., 2020 ; Yau et al ., 2021 ; Mejia et al ., 2022 ). Newspaper coverage of upstream drivers of food poverty and insecurity, or charitable food aid use were largely governmental ( Wells and Caraher, 2014 ; Knight et al ., 2018 ; Tikka, 2019 ; Price et al ., 2020 ; Yau et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower transportation and time costs remove potential barriers to accessing emergency food distribution sites, which also may help explain why the housing and transportation theme is the only social vulnerability theme that is negatively associated with EFT reception. Furthermore, news coverage during the pandemic focused on the challenges and severe needs of disadvantaged community members, along with their deservingness of emergency food assistance (Mejia et al, 2022 ). This news coverage could contribute to higher EFT reception in socially vulnerable neighborhoods, by increasing awareness of available resources and reducing stigma among local residents.…”
Section: Contributions and Policy Implicationsmentioning
confidence: 99%